PERAN KETELADANAN ORANG TUA KRISTEN DALAM PEMBENTUKAN KARAKTER ANAK USIA 6-12 TAHUN DI GEREJA BETHEL TABGHA - Robertus Suryady (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
The reality of a child's development and growth necessitates the assistance and guidance of both parents in providing support and serving as exemplary figures. Parents hold the greatest responsibility in the development of the overall existence of their children, including their physical and psychological needs, to enable them to grow and mature towards a harmonious and mature personality. This study is entitled